Behavior of parallel two-stage method for the simulation of steel solidification in continuous casting. (May 2019) - Garcia, T.; Spiteri, P.; Khenniche, G.
Highlights: The studied problem concerns the behavior of parallel two-stage method for the simulation of steel solidification in continuous casting. The model of the thermal process is described thanks to a non linear boundary value problems subjected to some constraints. We propose a tow-stage method for the solution of the model problem. The convergence of the numerical procedure is presented. Numerical synchronous and asynchronous parallel experiments are also presented. Abstract: This paper presents the behavior of general parallel synchronous and asynchronous multisplitting and two-stage methods for the numerical simulation of steel solidification in continuous casting. Thanks to the mathematical analysis and the implementation of these methods one can show the results of parallel experiments for the target application. The mathematical model is constituted by coupled nonlinear boundary value problems, namely the heat equation taking into account, on part of the boundary, a radiation phenomenon described by the Stefan law. For the numerical solution of such partial differential equations we consider, depending on whether the coefficient of thermal conductivity is constant or temperature-dependent, both an implicit or a semi-implicit discretization with respect to the time of the studied evolution problem, while the spatial discretization is carried out by adapted finite difference schemes. Then large scale discretized algebraic systems are solved by sequential and synchronous or asynchronous iterative algorithms; comparison of these various previous methods implemented on clusters and grid are achieved in both cases when the thermal conductivity is constant and more generally dependent of the temperature.